A 2007 Social Accounting Matrix (SAM) for Namibia - van Seventer, Dirk (International Food Policy Research Institute, 2014)
A 2007 Social Accounting Matrix (SAM) for Namibia is constructed using data that available during the second half of 2011. The national SAM is built using 2007 National Accounts data for Namibia, UN National Accounts Official Country Data, OECD/ADB African Economic Outlook data, a 2004 SAM, UNComTrade data and WB Development Indicators. The SAM provides a detailed representation of the Namibian economy. It separates 24 activities and 25 commodities; labor is disaggregated by 3 skill groups; and households into 6 groups based on the rural/urban and income status of the household head. The SAM is a useful database for conducting economy-wide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.